Associations of Anogenital Low-Risk Human Papillomavirus Infection With Cancer and Acquisition of HIV. Issue 10 (October 2015) - Bennetts, Liga E.; Wagner, Monika; Giuliano, Anna R.; Palefsky, Joel M.; Steben, Marc; Weiss, Thomas W.
<x xml:space="preserve">Abstract</x> ABSTRACT α-Mucosal human papillomavirus (HPV) types are implicated in a range of clinical conditions and categorized as "low-risk" (LR) and "high-risk" (HR) types according to their degree of association with cervical cancers. The causative role of LR HPV infection in the development of anogenital warts and in low-grade squamous intraepithelial lesions is well established. In addition, there is a growing body of evidence that infection with LR HPV types may be associated with an elevated risk of cancers and potentiation of coinfections. Prospective and case-control studies consistently report a higher risk of anogenital cancers in men and women with a history of anogenital warts. Based on currently available evidence, this higher risk may be due to shared exposure to HR HPV types or an underlying immune impairment, rather than a direct role of LR HPV types in subsequent cancer risk. Data also suggest that infection with LR HPV, HR HPV, or both may increase the risk of HIV acquisition, although the relative contribution of different HPV types is not yet known. There is also evidence implicating HPV clearance, rather than HPV infection, in increased risk of HIV acquisition.